K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

27 tháng 12 2016

\(Vì\left(x+2\right)^2\ge0\forall x\)

     \(\left(y+2\right)^2\ge0\forall x\)

\(Để\left(x+2\right)^2+\left(y+2\right)^2=0\Leftrightarrow\left(x+2\right)^2=0;\left(y+2\right)^2=0\)

\(\Rightarrow x=-2;y=-2\)

16 tháng 1 2018

a) \(2x^4+3x^3-16x-24=0\)

\(\left(2x^4+3x^3\right)-\left(16x+24\right)=0\)

\(x^3.\left(2x+3\right)-8\left(2x+3\right)=0\)

\(\left(x^3-8\right)\left(2x+3\right)=0\)

\(\Rightarrow\orbr{\begin{cases}x^3-8=0\\2x+3=0\end{cases}}\Rightarrow\orbr{\begin{cases}x^3=8\\2x=-3\end{cases}}\Rightarrow\orbr{\begin{cases}x=2\\x=\frac{-3}{2}\end{cases}}\)

vậy \(\orbr{\begin{cases}x=2\\x=-\frac{3}{2}\end{cases}}\)

28 tháng 8 2017

Ta có:

(x+y)2-(x-2)2=0

=>(x+y)2=(x-2)2

=>x+y=x-2

=>y+2=0

=> y=-2

=> x là số bất kì

KL